Caroline de Solar : mobiliser son réseau lors de l’affaire du sourd-muet de l’abbé de l’Épée - Géraldine Ther (Criminocorpus)
At the end of the eighteenth century, the Solar case attracted a lot of public attention. Famous people such as L’Abbé de l’Épée or Élie de Beaumont were involved. The young Caroline de Solar stayed in the shadows but played an important part. This penniless orphan managed to stand against the young man who pretended to be her deceased brother. To understand how, we need to analyse the networks surrounding her parents and her tutors, Marie-Françoise Julliot and Paul-Augustin Moreau de Vormes. We can use records from the Châtelet, but also numerous factums kept at the Bibliothèque nationale de France and tales from the Causes Célèbres.